ETIOLOGY AND PRESENTATION OF ACUTE BACTERIAL MENINGITIS IN CHILDREN AT AL-THAWRAH HOSPITAL - Sallam, Abdul Khaliq A. (Journal of Ayub Medical College Abbottabad, 2004)
Background: This study was carried out to determine the etiology and management outcome of acute bacterial meningitis among children presenting at Al-Thawrah hospital, Sana’a, Yemen. Methods: This study was carried out from 1-1/2001 to 23-8-2002. It initially included 77 children of all ages (newborn to 12 years), who attended pediatric emergency with fever, convulsions and altered sensorium. Full medical history, clinical examination and lab investigations were used to diagnose acute bacterial meningitis, and to summarize etiology, presentation and management outcome. Results: Over this 20 months period only 63 (81.81%) out of 77 suspected children were diagnosed as acute bacterial meningitis (ABM). The most affected age group was 4 months and 3 years. Based on CSF exam; there were 23 with positive findings of CSF analysis (turbid, decrease glucose <40mg.dl, increase protein >80mg.dl and leucocytes neutrophils >5cells.cu.mm), 21 cases were confirmed with CSF culture, while the remaining 19 cases showed normal CSF pictures. The fatality rate was 14.28%. The predominant organism in CSF culture was Klebsiella (33.33%) followed by Haemophilius influenza (23.80%), streptococcal pneumonia (14.28%) then 2 cases each; E-coli, Pseudomonas (9.52%) while with one cases each of tubercles meningitis and staphylococcus aureus. Conclusion: Proper knowledge of etiology and presentation of ABM along with timely vaccination can help reduce mortality and morbidity associated with this deadly disease. Key words: Acute bacterial meningitis, Etiology, Febrile convulsion, CSF culture